A nurse-led, telephone-based patient support program for improving adherence in patients with relapsing-remitting multiple sclerosis using interferon beta-1a: Lessons from a consumer-based survey on adveva® PSP - Barello, Serena; Paolicelli, Damiano; Bergamaschi, Roberto; Cottone, Salvatore; D'Amico, Alessandra; Annibali, Viviana; Paolillo, Andrea; Bosio, Caterina; Panetta, Valentina; Graffigna, Guendalina (Frontiers in Psychology, 2022)
Background. Evidence suggests that organizational models that provide care interventions including patient support programs may increase patient adherence to multiple sclerosis (MS) therapies by providing tailored symptom management, informational support, psychological and/or social support, lifestyle changes, emotional adjustment, health education, and tailored coaching, thus improving patients’ overall quality of life across the disease course. Objective. The main objective of this study was to describe MS patients’ self-reported experience of a nurse-led, telephone-based PSP and to explore its potential role in improving disease and therapy management skills. Methods. Survey data were analyzed from a subset of patients relapsing–remitting MS (RRMS) using interferon beta-1a already registered in the adveva® PSP from three Italian multiple sclerosis centers with a consolidated experience in RRMS disease, treatment management, and PSP programs. Results. In total, 244 patient data at baseline were analyzed, of which 115 had a follow-up of at least 6 months. Results from this study provide an early view into the role of this PSP in improving the patients reported overall experience regarding disease management and injectable therapy, thus potentially ameliorating treatment adherence and decreasing health care cost. Moreover, study findings confirm the role of providing a patient-focused support by addressing non-medication-related topics in the PSP consultations. Indeed, patients involved in the adveva® PSP program reported a better psychological status in the follow up as demonstrated by an increased optimism regarding their future, tolerance of disease uncertainty, and their perceived ability to benefit from external help and social support (informal caregivers). Conclusions. As such, it is reasonable to conclude that the involvement in the adveva® PSP and the PSP’s assistance in guiding patients on proper treatment self-management techniques is of great value to patients as it might contribute to improving engagement in their health care journey in terms of perceived self-care skills, emotional coping towards the future and the unpredictability of the disease course and their general attitudes towards the injection itself, involving pain tolerance.